Hormonal secretion and quality of life in Nelson syndrome and Cushing disease after long acting repeatable octreotide: a short series and update - Arregger, Alejandro Luis (2014)
Clinical management of persistent ACTH excess in Nelson´s syndrome (NS) and Cushing´s disease (CD) remains a challenge. Somatostatin (SS) and its analogs as octreotide decrease ACTH secretion through SS receptors (sst) of pituitary cells. To our knowledge there are no reports on the effect of long-acting repeatable octreotide (oct-lar) on hormonal secretion and quality of life in patients with NS and CD who failed conventional therapy. Herein we describe the effects of treatment with oct-lar (20 mg/ i.m. month) in one woman with NS and two women with persistent CD . Oct-lar therapy reduced ACTH secretion and improved quality of life in NS, by contrast in CD it failed to control ACTH and cortisol secretion and quality of life remained unchanged.